Case report: Prenatal diagnosis of Kagami–Ogata syndrome in a Chinese family - Hu, Junjie; Zhang, Ying; Yang, Yanmei; Wang, Liya; Sun, Yixi; Dong, Minyue (Frontiers in Genetics, 2022)
The aim was to explore the genetic cause of the proband (Ⅲ2) presenting with polyhydramnios and gastroschisis. Copy number variation sequencing (CNV-seq), methylation-specific multiplex PCR (MS-PCR), and methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA) were used to characterize the genetic etiology. CNV-seq revealed a deletion of 732.26kb at 14q32.2q32.31 in the proband (Ⅲ2) and its mother (Ⅱ2). MS-PCR showed the maternal allele was missing in the proband while paternal allele was missing in its mother. MS-MLPA showed homozigosity of the DLK1, MEG3, MIR380, and RT1 genes of both proband and its mother. MEG3 imprinting gene methylation was increased in the proband, while decreased in its mother. It was indicated that a maternally transmitted deletion was responsible for the Kagami–Ogata syndrome (KOS) in the proband (Ⅲ2) and the de novo paternal deletion resulted in Temple syndrome (TS) in the mother (Ⅱ2). Prenatal diagnosis was provided at 17+3 weeks’ of pregnancy on mother’s 4th pregnancy (Ⅲ4). Fortunately, the karyotype and single-nucleotide polymorphism array (SNP-array) results were normal. The current investigation provided the detection methods for imprinted gene diseases, expanded the phenotype spectrum of the disease, and got the insight into the diagnosis, prenatal diagnosis, genetic counseling of the disease.